Suprapatellar Versus Infrapatellar Tibial Nail Insertion: A Prospective Randomized Control Pilot Study. Issue 3 (March 2016) - Chan, Daniel S.; Serrano-Riera, Rafael; Griffing, Rebecca; Steverson, Barbara; Infante, Anthony; Watson, David; Sagi, H. Claude; Sanders, Roy W.
Abstract : Purpose: The purpose of this OTA-approved pilot study was to compare the clinical and functional outcomes of the knee joint after infrapatellar (IP) versus suprapatellar (SP) tibial nail insertion. Design: Prospective, randomized. Setting: Level I trauma center. Methods: After institutional review board approval, skeletally mature patients with OTA 42 tibial shaft fractures were randomized into either an IP or SP nail insertion group after informed consent was obtained. The SP also underwent prenail and postnail insertion patella-femoral (PF) joint arthroscopy. Patients underwent follow-up (6 weeks, 3, 6, and 12 months) with standard radiographs, as well as visual analog score and pain diagram documentation. At the 6-month and 12-month visits, knee function questionnaires (Lysholm knee scale and SF-36) were completed. Magnetic resonance imaging/image (MRI) of the affected knee was obtained at 12 months. Ten patients in each group were required for a power analysis for the anticipated larger randomized control trial, but enrollment in each arm was not limited because of known problems with patient follow-up over a 12-month period. Results: A total of 41 patients/fractures were enrolled in this study. Of those, only 25 patients/fractures (14 IP, 11 SP) fully complied with and completed 12 months of follow-up. Six of 11 SP presented with articular changes (chondromalacia) in the PF joint during the preinsertion arthroscopy. Three patients displayed a change in the articular cartilage based on postnail insertion arthroscopy. At 12 months, all fractures in both groups had proceeded to union. There were no differences between the affected and unaffected knee with respect to range of motion. Functional visual analog score and Lysholm knee scores showed no significant differences between groups ( P > 0.05). The SF-36v2 comparison also revealed no significant differences in the overall score, all 4 mental components, and 3/4 physical components ( P > 0.05). The bodily pain component score was superior in the SP group (45 vs. 36, P = 0.035). All 11 SP patients obtained MRIs at 1 year. Five of these patients had evidence of chondromalacia on MRI. These findings did not correlate with either the prenail or postnail insertion arthroscopy. Importantly, no patient in the SP group with postnail insertion arthroscopic changes had PF joint pain at 1 year. Conclusions: Overall, there seemed to be no significant differences in pain, disability, or knee range of motion between these 2 tibial intramedullary nail insertion techniques after 12 months of follow-up. Based on this pilot study data, larger prospective trial with long-term follow-up is warranted. Level of Evidence: Therapeutic Level II. See Instructions for Authors for a complete description of levels of evidence.